2008
DOI: 10.1007/s11255-008-9449-1
|View full text |Cite
|
Sign up to set email alerts
|

Vesico-vaginal fistula: report of 220 cases

Abstract: The total recurrence rate of 6.4% did not differ significantly between various procedures. However, TVAG is less invasive and suitable for uncomplicated cases, whereas TPA should be recommended for great and recurrent VVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…Our outcomes compare similarly to the 75% initial success rate reported by Ockim, et al in a series of 24 abdominal VVF repairs [7], but lower than those reported by Hadzi-Djokic (32 patients, 94% success) [8], and Rahjamaheswari (19 patients, 100%) [6]. It is challenging to compare outcomes between patient cohort's due to potentially differing demographics, definition of successful closure, and follow up.…”
Section: Discussionsupporting
confidence: 78%
“…Our outcomes compare similarly to the 75% initial success rate reported by Ockim, et al in a series of 24 abdominal VVF repairs [7], but lower than those reported by Hadzi-Djokic (32 patients, 94% success) [8], and Rahjamaheswari (19 patients, 100%) [6]. It is challenging to compare outcomes between patient cohort's due to potentially differing demographics, definition of successful closure, and follow up.…”
Section: Discussionsupporting
confidence: 78%
“…Abdominal approach is recommended if the ex- 27 posure is inadequate due to the lack of surgeon experience or due to a retracted fistula. Some surgeons recommended that abdominal approach should be considered for recurrent VVF or when the fistula was high and large (>3 cm) [26] . As shown in table 3 , vaginal approach was advocated regardless of primary or recurrent fistulas in our clinical center.…”
Section: Discussionmentioning
confidence: 99%
“…There are no randomised studies that compare the outcomes of transabdominal vs transvaginal approaches. Nonrandomised studies compared the outcomes of transvaginal vs transabdominal approaches for fistula repair [21,40,41]. The overall success rate for a vaginal approach was 91% vs 84% for abdominal repairs (P = 0.018).…”
Section: Outcome After Surgerymentioning
confidence: 99%